Workload and Organizational Citizenship Behavior on Employee Performance: The Mediating Role of Job Satisfaction - Alifah, Gita Dwi; Sulistyarini, Imbuh (Research Horizon, 2025)
Employee performance in public sector organizations is influenced by various factors, including workload, organizational citizenship behavior, and job satisfaction, yet their interplay remains underexplored. This study aims to examine the effects of workload and organizational citizenship behavior on employee performance, with job satisfaction as a mediating factor. Data were collected through an online survey from 321 employees at the Ministry of Finance of the Republic of Indonesia and analyzed using partial least squares structural equation modeling to evaluate relationships between variables. The findings reveal that organizational citizenship behavior and job satisfaction positively enhance employee performance, while workload does not significantly hinder it. Job satisfaction mediates the relationships between workload, organizational citizenship behavior, and employee performance, indicating that a supportive work environment can mitigate workload challenges. The study concludes that fostering organizational citizenship behavior and ensuring job satisfaction are critical for improving employee performance, even under demanding workloads. These insights offer practical guidance for public sector organizations to optimize human resource management, though further research is needed to explore these dynamics across diverse contexts.